A human iPSC-derived midbrain neural stem cell model of prenatal opioid exposure and withdrawal: A proof of concept study - Rhea Sullivan; Quinn Ahrens; Sara L. Mills-Huffnagle; Irina A. Elcheva; Steven D. Hicks (PLoS ONE, 2025)
A growing body of clinical literature has described neurodevelopmental delays in infants with chronic prenatal opioid exposure and withdrawal. Despite this, the mechanism of how opioids impact the developing brain remains unknown. Here, we developed an in vitro model of prenatal morphine exposure and withdrawal using healthy human induced pluripotent stem cell (iPSC)-derived midbrain neural progenitors in monolayer. To optimize our model, we identified that a longer neural induction and regional patterning period increases expression of canonical opioid receptors mu and kappa in midbrain neural progenitors compared to a shorter protocol (OPRM1, two-tailed t-test, p =  0.004; OPRK1, p =  0.0003). Next, we showed that the midbrain neural progenitors derived from a longer iPSC neural induction also have scant toll-like receptor 4 (TLR4) expression, a key player in neonatal opioid withdrawal syndrome pathophysiology. During morphine withdrawal, differentiating neural progenitors experience cyclic adenosine monophosphate overshoot compared to cell exposed to vehicle (p =  0.0496) and morphine exposure conditions (p, =  0.0136, 1-way ANOVA). Finally, we showed that morphine exposure and withdrawal alters proportions of differentiated progenitor cell fates (2-way ANOVA, F =  16.05, p <  0.0001). Chronic morphine exposure increased proportions of nestin positive progenitors (p =  0.0094), and decreased proportions of neuronal nuclear antigen positive neurons (NEUN) (p =  0.0047) compared to those exposed to vehicle. Morphine withdrawal decreased proportions of glial fibrillary acidic protein positive cells of astrocytic lineage (p =  0.044), and increased proportions of NEUN-positive neurons (p <  0.0001) compared to those exposed to morphine only. Applications of this paradigm include mechanistic studies underscoring neural progenitor cell fate commitments in early neurodevelopment during morphine exposure and withdrawal.